The Effect of Promotion, Store Atmosphere and Service Quality on Purchase Decision: The Covid-19 Pandemic - Tjahjaningsih, Endang; Nanda, Getcha Olivira; Marlien, RA; Cahyani, Alya Takwarina (Journal of Economics and Public Health, 2022)
This study aims to analyze the effect of promotion, store atmosphere and service quality on purchasing decisions. The population of this research is consumers who make purchases at Superindo supermarkets, Semarang, Indonesia, the number of which is not known with certainty. The sample in this study was 100 consumers. The sampling technique used was purposive sampling. The type of data used is primary. The data collection technique used is a questionnaire. The analysis technique used is descriptive analysis and multiple regression analysis. The results of the study show that: (1) Promotion has an effect on Purchase Decisions. (2) Store Atmosphere has an effect on Purchase Decision. (3) Service quality has an effect on purchasing decisions. Superindo should increase promotions by making advertisements in electronic media such as television and internet media as well as distributing brochures to consumers' homes, providing wider distances between displays and queuing distances at cashiers and providing delivery shopping services during the covid 19 pandemic.